Ticket pricing with different inventory information displays. (July 2017) - Huang, Yeu-Shiang; Wang, Jun-Guo; Ho, Jyh-Wen
Highlights: We consider different inventory display formats on the customers' perceived shortage risks. We develop an appropriate pricing strategy for the ticket seller to maximize his profits. In case of DN, customers would perceive the highest shortage risk. The less the information, the greater the perception of shortage risk, and thus the more the sales. The existences of speculators and strategic customers would reduce the risk of unsalable tickets. Abstract: This study considers a ticket seller who can use three different display formats: displaying all, displaying partial, and displaying no information, to reveal the number of remaining seats of the event, and determines the corresponding optimal pricing strategies when facing myopic and strategic customers as well as a speculator. We investigate the effects that the three different display formats have on the customers' willingness to make a purchase and the speculator's speculative behavior. The results show that displaying no information enables customers to guess the number of remaining tickets only based on the status of ticket sales when entering the market, and, as a result, they would perceive the highest shortage risk. Displaying partial information hinders customers with regard to accurately predicting the sales, which increases their perception of future shortage risk, and thus more strategic customers would purchase tickets at the presale stage. Additionally, this intensive purchase behavior would also attract more speculators to enter the market, which, would enhance the total sales and reduce the risk of unsalable tickets for the seller. With regard to profitability, the ticket seller earns the most profit when displaying no information, followed by displaying partial information and then displaying all information, since the less the information about remaining seats that is available, the greater the perception of shortage risk, and thus the more ticket sales that are made.